BIOLOGICAL CHARACTERISTICS OF ROUND SCAD DECAPTERUS MARUADSI (TEMMINCK & SCHLEGEL, 1843) IN THE TONKIN GULF - Son, Hoang Ngoc; Ha, Vu Viet (Vietnam Journal of Marine Science and Technology, 2016)
Biological characteristics of the round scad Decapterus maruadsi (Temminck & Schlegel, 1843) were analyzed using data collected by Vietnam - China Corporation Survey Project for the Marine Fisheries Resources Assessment in the Common Fishing Zone in the Gulf of Tonkin. Biological samples were monthly and randomly collected from the catches of trawl fisheries in Cat Ba island (Hai Phong) and Lach Hoi, Lach Bang (Thanh Hoa province). There were a total of 7,614 individuals of round scad collected in the period from 2012 - 2013. The result showed that the fork length of fish varied in range of 45 - 262 mm with the mean length from 166 - 167 mm. The Von Bertalanffy growth function of round scad was expressed as . Round scad spawned once a year with the spawning season extending from January to April and reaching a peak in March. The estimated length at first maturity (Lm50) was 160.96 mm for female and 161.37 mm for male.